2015
DOI: 10.1044/2015_jslhr-s-14-0203
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Submental Surface Electromyography and Hyo-Laryngeal Kinematic Measures of Mendelsohn Maneuver Duration

Abstract: Purpose The Mendelsohn Maneuver (MM) is a commonly prescribed technique that is taught to individuals with dysphagia to improve swallowing ability. Due to cost and safety concerns associated with videofluoroscopy (VFS) use, submental surface electromyography (ssEMG) is commonly used in place of VFS to train the MM in clinical and research settings. However, it is unknown whether ssEMG accurately reflects the prolonged hyo-laryngeal movements required for execution of the MM. The primary goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
1
20
0
2
Order By: Relevance
“…Their duration target was 2 seconds of increased ssEMG amplitude. Similar to Ding et al (2002), Crary et al (2004), and Azola et al (2015), a specific amplitude target threshold was not established. Instead, we aimed to simulate clinical use of ssEMG biofeedback without simultaneous complex analysis and interpretation of the EMG signal by the participant.…”
Section: Methodsmentioning
confidence: 66%
See 3 more Smart Citations
“…Their duration target was 2 seconds of increased ssEMG amplitude. Similar to Ding et al (2002), Crary et al (2004), and Azola et al (2015), a specific amplitude target threshold was not established. Instead, we aimed to simulate clinical use of ssEMG biofeedback without simultaneous complex analysis and interpretation of the EMG signal by the participant.…”
Section: Methodsmentioning
confidence: 66%
“…It is safe, widely available, and less expensive than videofluoroscopy. We used the same ssEMG recording procedures as Azola et al (2015). Bipolar ssEMG electrodes (Dual Bio Amp by AD Instruments) were placed on the left and right sides of the submental muscle group, approximately half way between the hyoid bone and the mentalis of the mandible.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the barriers in using VF or FEES for therapeutic purposes, submental surface EMG (ssEMG) is commonly employed in dysphagia management as a form of nonkinematic biofeedback because it is widely available, safe, and cost effective . The caveat of ssEMG is that it displays nonkinematic information, meaning that, although it can record and display the activation of muscle groups involved in swallowing, it cannot provide direct visualization of the movements of specific structures essential for airway protection and thus its effectiveness as a visual biofeedback tool in dysphagia management has been questioned . In fact, in a study with concurrent ssEMG and VF, Azola et al showed that when training a swallowing maneuver called the Mendelsohn Maneuver (involves prolonging elevation of the hyoid bone and larynx), changes in ssEMG while performing this maneuver represented less than 40% of the actual kinematics of the hyoid bone or larynx in both healthy adults and individuals poststroke .…”
Section: Introductionmentioning
confidence: 99%